Which factors determine adaptation to drought amongst farmers in Northern Thailand? Investigating farmers’ appraisals of risk and adaptation and their exposure to drought information communications as determinants of their adaptive responses - Sutcliffe, Chloe; Holman, Ian; Goodwin, Daniel; Salmoral, Gloria; Pardthaisong, Liwa; Visessri, Supattra; Ekkawatpanit, Chaiwat; Rey, Dolores (Mitigation and adaptation strategies for global change, 2024)
Drought communications constitute an important source of learning about climate risks and responses that can assist adaptation decision-making amongst those whose livelihoods are threatened by drought. This paper applies Protection Motivation Theory to explore associations between drought communications and attitudes towards drought risk and adaptation amongst farmers in Northern Thailand. The analysis reveals links between drought communications, farmers’ adaptation appraisal, and their adaptation decisions, whilst links with risk appraisal are minimal. The results highlight positive feedbacks between adaptation experience and appraisal and reveal a weak negative relationship between risk appraisal and adaptation appraisal. The findings imply benefits to framing drought communications in terms of the efficacy and attainability of suitable adaptations, rather than simply highlighting drought risks or providing drought warnings, to best enable farmers to build drought resilience.